2017
DOI: 10.7251/qol1701023j
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and Mercury Content Determination in Commercial Cosmetics Products by Atomic Absorption Spectroscopy

Abstract: Abstract:Toxic elements are present everywhere in nature and even in raw materials and pigments used in the manufacture of cosmetics. Human bodies daily exposed to toxic elements that can be found in trace amounts in cosmetic products. These elements such as arsenic and mercury can cause local skin damage or possible, their absorption through the skin or swallowed. In this paper we determined the content of arsenic and mercury in ten lipstick samples and eight nail polishes samples by atomic absorption spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…29 According to the research studies, it is known that Pb enters the body through the gastrointestinal tract and lungs, 30 it destroys red blood cells and reduces their oxygen-carrying capacity to necessary tissues, resulting in anaemia. 31 Cadmium Through research it is widely acknowledged that in the cosmetics Industry, Cd is used in colour pigments. It can be used in a variety of cosmetics, although it is most commonly found in lipstick, polluted air, cigarettes, and contaminated food.…”
Section: Health Impacts Of Heavy Metals and Other Constituents Of Lip...mentioning
confidence: 99%
See 1 more Smart Citation
“…29 According to the research studies, it is known that Pb enters the body through the gastrointestinal tract and lungs, 30 it destroys red blood cells and reduces their oxygen-carrying capacity to necessary tissues, resulting in anaemia. 31 Cadmium Through research it is widely acknowledged that in the cosmetics Industry, Cd is used in colour pigments. It can be used in a variety of cosmetics, although it is most commonly found in lipstick, polluted air, cigarettes, and contaminated food.…”
Section: Health Impacts Of Heavy Metals and Other Constituents Of Lip...mentioning
confidence: 99%
“…27 It has been shown to reduce gonadotropin binding, altering the activity of steroidogenic enzymes. 31 Furthermore, a synergistic impact between Pb, Cd, As, and Hg might result in cognitive impairment. 23 Chromium Cr levels were found to be highest in lipstick and eyeliner samples.…”
Section: Health Impacts Of Heavy Metals and Other Constituents Of Lip...mentioning
confidence: 99%
“…Nonetheless, it may cause skin rashes and scarring and reduce skin resistance to bacterial and fungal infections. Most importantly, being a neurotoxin, mercury exposure has been reported to cause adverse health effects in humans, especially neurological disorders including anxiety, depression, psychosis and peripheral neuropathy, as well as kidney dysfunction [ 1 , 2 ]. Monitoring the level of mercury ions (Hg 2+ ) in cosmetic products is therefore of fundamental importance.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional analytical methods for the detection of Hg 2+ usually rely on the use of advanced instruments based on spectrometric and chromatographic techniques, such as atomic absorption spectrometry (AAS) [ 1 , 5 ], inductively coupled plasma mass spectrometry (ICPMS) [ 6 ], graphite furnace atomic absorption spectrometry (GFAAS) [ 2 ], inductively coupled plasma atomic emission spectrometry (ICP-AES) [ 7 ] and liquid chromatography inductively coupled plasma mass spectrometry (LC-ICP-MS) [ 8 ]. While such approaches have been proven to be highly accurate and sensitive, the complex, expensive and time-consuming procedures associated with these methods call for a simpler alternative for daily analysis and on-site detection in a large number of samples in the field.…”
Section: Introductionmentioning
confidence: 99%
“…The highest proportion of Hg was observed in skin lightening creams (mean concentration 1.008 ppm). Heavy metals were found in cosmetic products of different countries markets in Khyber Pakhtunkhwa, Pakistan, Caribbean, Banja Luka (Jelić, Antunović, & Đermanović, 2017;Mohammed, Mohammed, & Bascombe, 2017;Ullah et al, 2017). In Vietnam, some authors have identified banned substances in cosmetics.…”
Section: Introductionmentioning
confidence: 99%